A Study On Skills Set Required For A Good Project Leader - Cheah, Eng How (2007)
The objective of the research is to find out what are the skills set needed to become a good project leader, especially in semiconductor manufacturing. Among the skills set, what are the top 2 most important project skills set, any significant different in term of top 2 skills set between gender and their education level.